Предмет:
МатематикаАвтор:
thaddeusl1q5Автор:
leandrogr11Автор:
mcgrathАвтор:
raisinАвтор:
elsaАвтор:
mauriciobecker√(6-t) – √(5-t) = 4
Умножим левую и правую части уравнения на √(6-t) + √(5-t)
(√(6-t) – √(5-t))(√(6-t) + √(5-t)) = 4 · (√(6-t) + √(5-t))
6 - t - 5 + t = 4 · (√(6-t) + √(5-t))
4 · (√(6-t) + √(5-t)) = 1
√(6-t) + √(5-t) = 0,25
Автор:
maverick8djeДобавить свой ответ
Предмет:
ХимияАвтор:
aubriehartmanОтветов:
Смотреть
Предмет:
АлгебраАвтор:
kaitlinvbwhОтветов:
Смотреть
Предмет:
МатематикаАвтор:
westОтветов:
Смотреть
Предмет:
ГеометрияАвтор:
sanaaglassОтветов:
Смотреть